Microstructural analysis on biochar obtained from rubber wood sawdust via slow pyrolysis - Norazman, Farhaneem; Se, Sian Meng; Dimin @ Mohd Amin, Mohd Fairuz; Shaaban, Azizah (Trans Tech Publications Ltd., 2017)
Biochar was derived from the crop residue as multifunction materials for agriculture purposes and a soil amendment to improve soil fertility. Rubber wood sawdust (RWSD) was heated slowly inside the vertical furnace for an hour at temperatures ranging from 300 °C to 700 °C. The aim of this study is to investigate the influence of pyrolysis temperatures on the physiochemical properties of the biochar. The properties of biochar were characterized using X-ray diffraction (XRD) and scanning electron microscope (SEM) attached with Energy Dispersive X-ray for elemental analysis. It was found that pore size distribution was more uniform on samples heated at higher temperature (700 °C). The SEM-EDX analysis confirmed the O:C ratio was directly proportional to the heating temperature. These means that slow pyrolysis of RWSD at 700 °C could produce biochar of greater cation exchange capacity (CEC) that important for soil fertility improvement.